Role of cerebral cortex in the neuropathology of Huntington's disease - Estrada-Sánchez, Ana M.; Rebec, George V. (Frontiers in Neural Circuits, 2013)
An expansion of glutamine repeats in the N-terminal domain of the huntingtin protein leads to Huntington´s disease (HD), a neurodegenerative condition characterized by the presence of involuntary movements, dementia, and psychiatric disturbances. Evaluation of postmortem HD tissue indicates that the most prominent cell loss occurs in cerebral cortex and striatum, forebrain regions in which cortical pyramidal neurons (CPNs) and striatal medium spiny neurons (MSNs) are the most affected. Subsequent evidence obtained from HD patients and especially from transgenic mouse models of HD indicates that long before neuronal death, patterns of communication between CPNs and MSNs become dysfunctional. In fact, electrophysiological signaling in transgenic HD mice is altered even before the appearance of the HD behavioral phenotype, suggesting that dysfunctional cortical input to the striatum sets the stage for the emergence of HD neurological signs. Striatal MSNs, moreover, project back to cortex via multi-synaptic connections, allowing for even further disruptions in cortical processing. An effective therapeutic strategy for HD, therefore, may lie in understanding the synaptic mechanisms by which it dysregulates the corticostriatal system. Here, we review literature evaluating the molecular, morphological, and physiological alterations in the cerebral cortex, a key component of brain circuitry controlling motor behavior, as they occur in both patients and transgenic HD models.